Biosynthesis of very long chain fatty acids in Trypanosoma cruzi - Livore, Veronica Ines (2015)
Trypanosoma brucei and Trypanosoma cruzi showed similar fatty acid (FA) compositions, having a high proportion of unsaturated FAs, mainly 18:2Δ9,12 (23–39 %) and 18:1Δ9 (11–17 %). C22 polyunsaturated FAs are in significant amounts only in T. brucei (12–20 %) but represent a mere 2 % of total FAs in T. cruzi. Both species have also similar profiles of medium- and long-chain saturated FAs, from 14:0 to 20:0. Interestingly, procyclic and bloodstream forms of T. brucei lack very long chain FAs (VLCFAs), whereas epimastigotes and trypomastigotes of T. cruzi contain 22:0 (0.1–0.2 %), 24:0 (1.5–2 %), and 26:0 (0.1–0.2 %). This is in agreement with the presence of an additional FA elongase gene (TcELO4) in T. cruzi. TcELO4 was expressed in a Saccharomyces cerevisiae mutant lacking the endogenous ScELO3, rescuing the synthesis of saturated and hydroxylated C26 FAs in the yeast. Expression of TcELO4 also rescued the synthetic lethality of a ScELO2, ScELO3 double mutation, and the VLCFA profile of the transformed yeast was similar to that found in T. cruzi. By identifying TcELO4 as the enzyme responsible for the elongation of FA from 16:0 and 18:0 up to 26:0, with 24:0 being the preferred product, this work completed the characterization of FA elongases in Trypanosoma spp.